2021
DOI: 10.1111/rssa.12738
|View full text |Cite
|
Sign up to set email alerts
|

A Downscaling Approach to Compare COVID-19 Count Data from Databases Aggregated at Different Spatial Scales

Abstract: As the COVID-19 pandemic continues to threaten various regions around the world, obtaining accurate and reliable COVID-19 data is crucial for governments and local communities aiming at rigorously assessing the extent and magnitude of the virus spread and deploying efficient interventions. Using data reported between January and February 2020 in China, we compared counts of COVID-19 from near-real-time spatially disaggregated data (city level) with fine-spatial scale predictions from a Bayesian downscaling reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…A location 1% farther away from an airport decreases the (log) COVID‐19 risk by 0.5% on average while keeping all other explanatory variables constant. Both logged traffic intensity (log(TRAFFIC)) and logged population (log(POP)) are associated with an increase in the logged COVID‐19 risk, which is consistent with the literature (Bhadra et al, 2021; Python et al, 2022; Zhang et al, 2020).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A location 1% farther away from an airport decreases the (log) COVID‐19 risk by 0.5% on average while keeping all other explanatory variables constant. Both logged traffic intensity (log(TRAFFIC)) and logged population (log(POP)) are associated with an increase in the logged COVID‐19 risk, which is consistent with the literature (Bhadra et al, 2021; Python et al, 2022; Zhang et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…Larger population density increases the pool of individuals to be infected and quickens the spread of the virus (Bhadra et al, 2021 ). Population is considered to be a major driver associated with the transmission of the COVID‐19 at various spatial scales (Python et al, 2022 ; Zhang et al, 2020 ). Therefore, we expect more vulnerability to COVID‐19 outbreaks close to densely populated areas.…”
Section: Spatial Propagation Model: a Hierarchical Bayesian Geostatis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation studies have shown promise but have raised questions (e.g., the ability for it to accurately specify fine‐scale patterns from aggregated data) about the appropriate usage of this method in real‐world scenarios (Arambepola et al, 2022). While not previously used in an applied ecological context, it has been successfully applied to disease risk modeling for COVID‐19 (Python et al, 2022) and malaria (Lucas et al, 2022). This approach does, however, build upon similar methodological studies implemented in ecology that downscales binary presence/absence species distribution model predictions to produce higher‐resolution predictions using a hierarchal approach (Keil et al, 2013).…”
Section: Introductionmentioning
confidence: 99%